Urgensi Keterwakilan Legislator Perempuan Dalam Lembaga Dewan Perwakilan Rakyat Republik Indonesia - Andreas, Ricco; Dela Putri Dwinanda; Jufinley Santoso; Windy Rizky Putri; Rizki Amaliah (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to examine the level of women’s representation in Indonesia’s legislative bodies and to explore the factors contributing to the low level of women’s political participation in decision-making processes. Employing a normative legal research method with a library research approach, this study collects and analyzes data from relevant literature. The focus is on the development of the 30% gender quota for women’s representation as stipulated in legislation, as well as its implementation in legislative elections, particularly the 2024 General Election. The findings indicate that although women’s representation has gradually increased over the years, the figure remains below the ideal quota target. In the 2024 election, for instance, only 127 seats, or 21.9% of the total 580 seats in the House of Representatives (DPR RI), were held by women. Several barriers contribute to this shortfall, including structural constraints, the dominance of patriarchal culture, limited political education, and a lack of support for female candidates. Nevertheless, women’s participation in the legislature is crucial for advancing gender-responsive policies, as reflected in the advocacy for the enactment of the Sexual Violence Crimes Bill. Therefore, strengthening women’s involvement in politics constitutes a strategic step toward building a more inclusive and equitable democracy.